An Editorial Introduction to Critical Thinking in Everyday Settings - Christopher P. Dwyer (Journal of Intelligence, 2025)
When I was first invited to guest edit a Special Issue of the Journal of Intelligence on critical thinking (CT), I was quite excited by the prospect for what I saw as two important reasons [...]